2008
DOI: 10.1007/s00441-008-0633-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mesenchymal tissues-derived stem cells for in vivo chondrogenesis: suitable conditions for cell therapy of cartilage defects in rabbit

Abstract: We previously compared mesenchymal stem cells (MSCs) from a variety of mesenchymal tissues and demonstrated that synovium-MSCs had the best expansion and chondrogenic ability in vitro in humans and rats. In this study, we compared the in vivo chondrogenic potential of rabbit MSCs. We also examined other parameters to clarify suitable conditions for in vitro and in vivo cartilage formation. MSCs were isolated from bone marrow, synovium, adipose tissue, and muscle of adult rabbits. Proliferation potential and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
242
3
7

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(256 citation statements)
references
References 28 publications
4
242
3
7
Order By: Relevance
“…Regarding aggrecan expression, BMSC respond better to TGFβ, while ASC require BMP-6 (Jakobsen et al, 2009) Human In hyaluronic acid scaffolds chondrogenesis of BMSC was higher compared to ASC (Liu et al, 2007) Human BMSC differentiate better into osteoblasts and chondrocytes, while ASC have higher adipogenic differentiation potential (Afizah et al, 2007) Human BMSC and ASC from the same donor: BMSC are more suitable for cartilage tissue engineering than ASC (Huang et al, 2005) Human A patient-matched study: under the described conditions, BMSC demonstrated a higher chondrogenic potential (Im et al, 2005) Human Results of this study suggest that ASC have inferior capacity for chondrogenic differentiation (Winter et al, 2003) Human There are no differences in the expression of chondrogenic marker genes in 2D cultures between ASC and BMSC. In 3D cultures BMSC expressed a gene profile similar to that of osteoarthritic cartilage (Koga et al, 2008) Rabbit BMSC have higher chondrogenic potential compared to ASC in vitro and in vivo Rat There are no major differences between ASC and BMSC regarding the chondrogenic differentiation potential (Kisiday et al, 2008) Equine Superior chondrogenesis of BMSC was demonstrated in comparison to ASC (Vidal et al, 2008) Equine Superior chondrogenesis of BMSC was demonstrated in comparison to ASC Table 2. Differences in surface marker expression of HLA-ABC in BMSC, making ASC more suitable for allogenic transplantations.…”
Section: Referencementioning
confidence: 94%
See 1 more Smart Citation
“…Regarding aggrecan expression, BMSC respond better to TGFβ, while ASC require BMP-6 (Jakobsen et al, 2009) Human In hyaluronic acid scaffolds chondrogenesis of BMSC was higher compared to ASC (Liu et al, 2007) Human BMSC differentiate better into osteoblasts and chondrocytes, while ASC have higher adipogenic differentiation potential (Afizah et al, 2007) Human BMSC and ASC from the same donor: BMSC are more suitable for cartilage tissue engineering than ASC (Huang et al, 2005) Human A patient-matched study: under the described conditions, BMSC demonstrated a higher chondrogenic potential (Im et al, 2005) Human Results of this study suggest that ASC have inferior capacity for chondrogenic differentiation (Winter et al, 2003) Human There are no differences in the expression of chondrogenic marker genes in 2D cultures between ASC and BMSC. In 3D cultures BMSC expressed a gene profile similar to that of osteoarthritic cartilage (Koga et al, 2008) Rabbit BMSC have higher chondrogenic potential compared to ASC in vitro and in vivo Rat There are no major differences between ASC and BMSC regarding the chondrogenic differentiation potential (Kisiday et al, 2008) Equine Superior chondrogenesis of BMSC was demonstrated in comparison to ASC (Vidal et al, 2008) Equine Superior chondrogenesis of BMSC was demonstrated in comparison to ASC Table 2. Differences in surface marker expression of HLA-ABC in BMSC, making ASC more suitable for allogenic transplantations.…”
Section: Referencementioning
confidence: 94%
“…A considerable number of papers have been published since 2003, addressing the question of which cell type, ASC or BMSC, possesses a higher chondrogenic potential (Table 1). A variety of authors concluded that BMSC can be more easily differentiated towards the chondrogenic lineage than ASC (Afizah et al, 2007;Danisovic et al, 2009;Huang et al, 2005;Im et al, 2005;Jakobsen et al, 2009;Kisiday et al, 2008;Koga et al, 2008;Liu et al, 2007;Vidal et al, 2008). However, Diekman et al (2010) pointed out that ASC and BMSC require unequal growth factor treatment for chondrogenic induction.…”
Section: The Potential Of Msc To Improve the State Of The Artmentioning
confidence: 99%
“…Scaffolds may further be defined as ''smart scaffolds'' if they carry with them some type of signal that can direct appropriate tissue formation either from the implanted cell type or from the surrounding resident cellular population. With respect to the delivery of synoviocytes for cartilage (hyaline or fibrocartilage) engineering, a number of different systems have been investigated including hydrogels (alginate [53,66] collagen [51,63,94], and gellan [28]), pellet cultures [63,80], micromasses [3,66], small intestinal submucosa (SIS) [84], hyaluronan-based scaffolds (Hyaff-111; FAB, Abano Terme, Padova, Italy) [56], polyglycolic acid (PGA) [67,74], PGA/poly (L) lactic acid (PLLA) combinations [34], and scaffold-free cell infusions [44,60]. With relatively few studies directly comparing delivery methods, elucidating an optimal carrier or scaffold from the literature alone is difficult.…”
Section: Scaffoldsmentioning
confidence: 99%
“…However, the surgical applicability of small spheroid pellets is somewhat limited for many large chondral applications. Hence, for articular cartilage, recent developments of a variety of hydrogel carriers that can suspend synoviocytes in three dimensions while filling discrete chondral defects have been investigated [28,51,53,63,66,94]. For meniscal applications, however, the need for tissue regeneration frequently resides in the avascular portion of the tissue, which may not exist as a singular defect with complete borders, thus posing a highly unstable and challenging environment for the surgical implantation of an engineered structure.…”
Section: Scaffoldsmentioning
confidence: 99%
“…Les CSM adultes semblent être de bonnes candidates pour l'IT du cartilage, puisqu'elles sont capables de se différencier vers le lignage chondrogénique [4] (Figure 1). Parmi les différentes sources de CSM, celles qui proviennent de la membrane synoviale présentent le meilleur potentiel de différenciation chondrogénique en termes de cinétique de diffé-renciation, de prolifération et de quantité de protéines matricielles produites in vitro, mais également en termes de réparation de lésions cartilagineuses in vivo [5]. La différenciation chondrogénique des CSM est décrite comme reproduisant le processus d'ossification endochondrale [6].…”
Section: Les Cellules Souches En Ingénierie Du Cartilage Articulaireunclassified